Pendekatan Guru Dalam Mengelola Perubahan Emosional Siswa Kelas V Selama Masa Pubertas Di SD Negeri 4 Sungai Buluh - Mahfuzah; Ahmad Suriansyah; Arta Mulya Budi Harsono; Bagus Aulia Iskandar; Diani Ayu Pratiwi (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The purpose of this study is to explore the strategies implemented by teachers in managing the emotional changes of fifth-grade students during puberty at SD Negeri 4 Sungai Buluh. This research employs a qualitative approach, involving both teachers and fifth-grade students. Data collection methods include observations, interviews, and documentation. Data analysis is conducted inductively through three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the emotional changes experienced by students during puberty require special attention from teachers. Strategies to address these issues include a patient and understanding approach, open communication, clear yet flexible boundaries, emotional understanding, confidence building, and social skills development